Regenerator site selection in impairment-aware elastic optical networks - Dharmaweera, M. N.; Yan, L.; Zhao, J.; Karlsson, M.; Agrell, E. (My University, 2016)
We propose a novel regenerator site selection scheme for nonlinear impairment-aware elastic optical networks. The proposed scheme reduces bandwidth use by up to 40% in a realistic network by employing only 6 regenerator sites.